2018
DOI: 10.1016/j.jmbbm.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Kinematics of collagen fibers in carotid arteries under tension-inflation loading

Abstract: Biomechanics of the extracellular matrix in arteries determines their macroscopic mechanical behavior. In particular, the distribution of collagen fibers and bundles plays a significant role. Experimental data showed that in most arterial walls there are preferred fiber directions. However, the realignment of collagen fibers during tissue deformation is still controversial: whilst authors claim that fibers should undergo affine deformations, others showed the contrary. In order to have an insight about this im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 60 publications
(109 reference statements)
3
29
0
Order By: Relevance
“…The wavelengths of the individual collagen fibrils observed in Krasny et al. (), which are two to three times the fibril thickness, 60 nm (Hansen et al. ), are not observed at the magnification used in this study, where the pixel resolution was 500 nm.…”
Section: Methodsmentioning
confidence: 49%
See 1 more Smart Citation
“…The wavelengths of the individual collagen fibrils observed in Krasny et al. (), which are two to three times the fibril thickness, 60 nm (Hansen et al. ), are not observed at the magnification used in this study, where the pixel resolution was 500 nm.…”
Section: Methodsmentioning
confidence: 49%
“…2C, where MATLAB (R2017b, Math-Works Inc., Natick, MA, USA) based von Mises mixture models is fit to the individual datasets to estimate the number of fibre families present based on the log-likelihood function (Hung et al 2012;Schymura, 2019). The wavelengths of the individual collagen fibrils observed in Krasny et al (2018), which are two to three times the fibril thickness, 60 nm (Hansen et al 2009), are not observed at the magnification used in this study, where the pixel resolution was 500 nm. Therefore, the individual fibril undulations did not affect the von Mises distributions measured.…”
Section: Polarised Light Microscopymentioning
confidence: 62%
“…At the same time, it is obvious that the deviations of model predictions from experiments beyond k z > 0.35 nm −1 may motivate additional investigations toward a more refined ultrastructural representation, and also the prediction of SAXS patterns emerging through bone under mechanical load, based on devices pioneered by Gupta et al [111,114] and Karunaratne et al [115], appears as an interesting topic for the future. At the same time, the current developments may also serve as a basis for a deeper investigation of configurational changes provoked by excessive mechanical loading of soft tissues, such changes having gained recent interest both experimentally [116,117], and computationally [118].…”
Section: Discussionmentioning
confidence: 99%
“…While this concept frequently provided very satisfactory results, in particular so in the context of mitral valve leaflet modeling, we also note several experimental observations where the fibers do not follow such a deformation pattern. These observations concern the adventitia layer of carotid arteries, but also tissues beyond the cardiac realm, such as the human liver capsule and murine skin . Typically, the aforementioned deformation patterns are associated with large shear strains in the soft matrix being situated in‐between the fibers; and such discrepancies between macroscopic and microscopic strains, being incompatible with affine deformation characteristics, have also been reported for tendon fascicles .…”
Section: Introductionmentioning
confidence: 93%